2007
DOI: 10.1144/sp286.35
|View full text |Cite
|
Sign up to set email alerts
|

Microstratigraphy of the Late Ediacaran to the Ordovician in NW Iran (Takab area)

Abstract: Platform sediments of Iran span the Late Ediacaran and extend into the Palaeozoic. They are primarily clastic and carbonaceous in nature, deposited in coastal and lagoonal settings. They crop out in the Takab area, as the Soltanieh Formation (Late Proterozoic to Atdabanian), the Barut Formation (Early Bottomian), the Zaigun Formation (Middle Bottomian), the Lalun Formation (Late Bottomian) and the Mila Formation (Middle Cambrian to Early Ordovician). A Precambrian–Cambrian assemblage has been identified at the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…The Soltanieh Formation is composed of five members; from base to top these are (Hamdi, Brasier & Zhiwen, 1989) the Lower Dolomite Member (LDM), the Lower Shale Member (LSM; Chopoghlu Shale), the Middle Dolomite Member (MDM), the Upper Shale Member (USM) and the Upper Dolomite Member (UDM). The PC-C boundary in the Soltanieh Formation is identified based on biostratigraphy; the majority of previous studies have established that this boundary is located near the top of the LSM, where early skeletal fossils such as Protohertzina anabarica and index trace fossils such as Treptichnus pedum appear in the succession (Hamdi, Brasier & Zhiwen, 1989;Ciabeghodsi et al 2005Ciabeghodsi et al , 2006Ciabeghodsi, 2007;Jafari, Shemirani & Hamdi, 2007). The MDM, USM and UDM contain a rich assemblage of small shelly fauna, which are similar to the well-documented lower Cambrian strata of the Nemakit-Daldyn Formation in Siberia and southern and central Asia (Hamdi, Brasier & Zhiwen, 1989;Kimura et al 1997;Kimura & Watanabe, 2001;Ciabeghodsi et al 2005Ciabeghodsi et al , 2006Ciabeghodsi, 2007;Jafari, Shemirani & Hamdi, 2007).…”
Section: Geological Setting and Stratigraphy Of The Soltanieh Formationmentioning
confidence: 99%
See 2 more Smart Citations
“…The Soltanieh Formation is composed of five members; from base to top these are (Hamdi, Brasier & Zhiwen, 1989) the Lower Dolomite Member (LDM), the Lower Shale Member (LSM; Chopoghlu Shale), the Middle Dolomite Member (MDM), the Upper Shale Member (USM) and the Upper Dolomite Member (UDM). The PC-C boundary in the Soltanieh Formation is identified based on biostratigraphy; the majority of previous studies have established that this boundary is located near the top of the LSM, where early skeletal fossils such as Protohertzina anabarica and index trace fossils such as Treptichnus pedum appear in the succession (Hamdi, Brasier & Zhiwen, 1989;Ciabeghodsi et al 2005Ciabeghodsi et al , 2006Ciabeghodsi, 2007;Jafari, Shemirani & Hamdi, 2007). The MDM, USM and UDM contain a rich assemblage of small shelly fauna, which are similar to the well-documented lower Cambrian strata of the Nemakit-Daldyn Formation in Siberia and southern and central Asia (Hamdi, Brasier & Zhiwen, 1989;Kimura et al 1997;Kimura & Watanabe, 2001;Ciabeghodsi et al 2005Ciabeghodsi et al , 2006Ciabeghodsi, 2007;Jafari, Shemirani & Hamdi, 2007).…”
Section: Geological Setting and Stratigraphy Of The Soltanieh Formationmentioning
confidence: 99%
“…These two shale members are separated by a dolomite member. The PC-C boundary is located almost at the top of the Lower Shale Member of the Soltanieh Formation, 200-300 m above its basal contact with the Kahar Formation as documented by biostratigraphic data (Hamdi, Brasier & Zhiwen, 1989;Ciabeghodsi et al 2005Ciabeghodsi et al , 2006Ciabeghodsi, 2007;Jafari, Shemirani & Hamdi, 2007;Ghorbani, 2013). However, Shahkarami, Mángano & Buatois (2017) have recently suggested that the Ediacaran-Cambrian boundary is located at the base of the Soltanieh Formation.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Late Ediacaran fossils from the Lower Shale Member (Chopoqlu Shale) of the Soltanieh Formation of northern Iran 18 and shale deposits of the Kushk Series in central Iran 19 – 21 include the type material of Permedusites changazensis Hahn and Pflug 1980, however previous reports of Dickinsonia? , Palaeoplatoda?…”
Section: Introductionmentioning
confidence: 99%
“…, and Kushkia? require further investigation in light of recent taxonomic and taphonomic studies 18 – 21 . Here we report the discovery of several new field sites from central Iran (Fig.…”
Section: Introductionmentioning
confidence: 99%